The persistence of memory Remembering slavery in Liverpool, 'slaving capital of the world' - Moody, Jessica (Liverpool University Press, 2020)
The Persistence of Memory is a history of the public memory of transatlantic slavery in the largest slave-trading port city in Europe, from the end of the 18th century into the 21st century; from history to memory. Mapping this public memory over more than two centuries reveals the ways in which dissonant pasts, rather than being 'forgotten histories', persist over time as a contested public debate. This public memory, intimately intertwined with constructions of 'place' and 'identity', has been shaped by legacies of transatlantic slavery itself, as well as other events, contexts and phenomena along its trajectory, revealing the ways in which current narratives and debate around difficult histories have histories of their own. By the 21st century, Liverpool, once the 'slaving capital of the world', had more permanent and long-lasting memory work relating to transatlantic slavery than any other British city. The long history of how Liverpool, home to Britain's oldest continuous black presence, has publicly 'remembered' its own slaving past, how this has changed over time and why, is of central significance and relevance to current and ongoing efforts to face contested histories, particularly those surrounding race, slavery and empire.